1991
DOI: 10.1002/kin.550230704
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the reactions of IO, BrO, and ClO with dimethylsulfide

Abstract: The kinetics of the reactions of 10, BrO, and C10 with DMS have been investigated at 298 K and total pressures of 0.5-6.8 mbar He using the discharge flow-mass spectrometry technique to monitor the halogen oxide radicals. Rate coefficients of (8.8 (2.7 f 0.5) x cm3 molecule-' 8-l have been obtained for the reactions of 10, BrO, and C10 with DMS, respectively. The result for I 0 with DMS is in good agreement with two other recent studies on this reaction but is nearly three orders of magnitude slower than two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 26 publications
(33 reference statements)
10
74
3
Order By: Relevance
“…Von Glasow et al (2004) showed that including halogen chemistry and specifically BrO into atmospheric chemistry transport models, led to an increase of 63% DMSO globally. Barnes et al (1991) found that BrO also adds to DMS which has a major impact on our OH dominated calculations for MSA and could account for the high MSA:nss-SO 4 2− ratios (Fig. 6).…”
Section: Impact Of Bro Mixing Ratios On the Oxidation Of Dmsmentioning
confidence: 88%
See 1 more Smart Citation
“…Von Glasow et al (2004) showed that including halogen chemistry and specifically BrO into atmospheric chemistry transport models, led to an increase of 63% DMSO globally. Barnes et al (1991) found that BrO also adds to DMS which has a major impact on our OH dominated calculations for MSA and could account for the high MSA:nss-SO 4 2− ratios (Fig. 6).…”
Section: Impact Of Bro Mixing Ratios On the Oxidation Of Dmsmentioning
confidence: 88%
“…In recent years the reaction of DMS + BrO has been explored and found to be 60% faster than previously reported by Barnes et al (1991) leading to a rate which is one order of magnitude slower than that for DMS+OH (Ingham et al, 1999). Considering BrO is often present in significantly higher atmospheric mixing ratios than OH this has an important impact on the rate of production of DMSO and hence also of MSA via the DMS+BrO route.…”
Section: Introductionmentioning
confidence: 95%
“…Atmospheric sources of radon are land-based whereas DMS is of oceanic origin (Ferek et al, 1995); therefore, the concentrations of these species are expected to be smaller in air masses that have been exposed to ICE rather than land or open water. Additionally, DMS can react with BrO (Barnes et al, 1991), which is an intermediate species that is present in elevated levels during ODEs (Hausmann and Platt, 1994;Neuman et al, 2010). Therefore, the oxidation of DMS by BrO would further enhance the negative correlation between DMS and ICE exposure.…”
Section: Correlations Between Other Gases and Modeled Sea Ice Exposurementioning
confidence: 99%
“…In the gas phase it is produced through the OHaddition channel, with a yield of approximately 30% of the total reaction at 298 K and as high as 70% at lower temperatures (Hynes and Wine, 1996;Arsene et al, 1999). In the case of XO-initiated atmospheric DMS oxidation (X = Br, Cl), DMSO yield is expected to be around 100% (Barnes et al, 1991;Ingham et al, 1999). DMSO is also produced via multiphase reactions of DMS with O 3 (Lee and Zhu, 1994).…”
Section: Dmsomentioning
confidence: 99%